El saldo a favor del impuesto a la renta y la compensación – límites - Gallardo Quiroz, Marisela (2021)
The author, through this essay, intends to expose about the Tax Credit, explaining its relationship with the Value Added Tax and, above all, with the concept of the balance in favor of income tax and its compensation. Therefore, the weight of the declaration of the debtor and the participation of the Tax Administration in this process are mentioned.